Food Safety Management Systems ISO 22000: 2018 And Its Implementation in The European Union Countries - Marcin Olkiewicz; Radosław Wolniak (Communications of International Proceedings, 2021)
The publication presents issues concerning the implementation of the food safety management standard ISO 22000:2018 in European Union countries. The research sought answers to questions such as: Which countries of the European Union have the largest number of organizations implementing food safety management systems compliant with ISO 22000:2018 requirements? Which countries have the highest saturation of ISO 22000:2018 certificates measured as number of certificates per million inhabitants? Can any regularities (income, geographic) be found between the implementation of ISO 22000:20018 certified food safety management systems in different countries and what might be their reasons? The analysis of the collected data allowed us to discover the interesting phenomenon of the occurrence of a negative, statistically significant, correlation between country wealth and the implementation of food safety management certification at -0.43
Keywords: Food Safety; Quality; Certificate; Management System